2017
DOI: 10.3390/ani7030022
|View full text |Cite
|
Sign up to set email alerts
|

Of Fur, Feather, and Fin: Human’s Use and Concern for Non-Human Species

Abstract: Simple SummaryAn online survey of 825 U.S. residents was conducted to determine the level of approval for several uses of animals. More than 90% of respondents reported that using animals for egg production, service or therapy, pets, and milk production was acceptable to them. Older and male respondents more frequently found most of the animal uses surveyed acceptable. Half of respondents reported concern for the welfare of bison while 40% or more stated concern for the welfare of elk, beef cattle, and dairy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 16 publications
3
13
1
Order By: Relevance
“…In dairy cattle, mastitis is a major cause of biological inefficiency or waste, for example, through lower yields, increased culling, discarded milk and impacts on fertility (Halasa et al, 2007;Seegers, Fourichon, & Beaudeau, 2003). In addition, mastitis affects animal welfare, which is highly valued in many industrialized countries (Byrd, Widmar, & Fulton, 2017;Tremetsberger, Leeb, & Winckler, 2015). Thus, there are many reasons to control mastitis in dairy cattle.…”
mentioning
confidence: 99%
“…In dairy cattle, mastitis is a major cause of biological inefficiency or waste, for example, through lower yields, increased culling, discarded milk and impacts on fertility (Halasa et al, 2007;Seegers, Fourichon, & Beaudeau, 2003). In addition, mastitis affects animal welfare, which is highly valued in many industrialized countries (Byrd, Widmar, & Fulton, 2017;Tremetsberger, Leeb, & Winckler, 2015). Thus, there are many reasons to control mastitis in dairy cattle.…”
mentioning
confidence: 99%
“…Concern for farm animal welfare varies across Europe, but is generally stronger in Northern countries such as the UK and Germany, and more pronounced among people not directly involved in farming [13,14]. In a US-based survey, over 90% of respondents reported that using animals for egg production was acceptable to them, although 38% expressed some concern for the welfare of chickens [35]. The observation that the majority of egg boxes (31/50) examined in this study express some message regarding hen welfare (Table 2), reflects how the industry acknowledges this concern amongst consumers [5].…”
Section: Hen: Disenfranchised Producersmentioning
confidence: 99%
“…For comparison, societal awareness of the importance of biodiversity is a more mature social issue than animal welfare and matured rapidly throughout the 1990s (Hill et al ) to the point where it would be widely considered to be a normalized issue today. Over the past 2 decades, animal welfare has expanded from a fringe movement in the emergence phase to a mainstream societal concern approaching normalization in many post‐industrial countries (Byrd et al ).…”
Section: The Rise Of Animal Welfarementioning
confidence: 99%